Criminal Justice System for Children Perpetrators of Murder Between Indonesia and Malaysia - Ridwansyah, Naufal Nabiil; Harefa, Beniharmoni (RechtIdee, 2024)
This study examines the comparative juvenile justice systems for child offenders of murder between Indonesia and Malaysia. The background of the research stems from the rising cases of children in conflict with the law due to serious crimes such as murder. Both countries adopt different legal approaches: Indonesia applies restorative justice through Law No. 11 of 2012 on the Juvenile Criminal Justice System, while Malaysia relies on the Child Act 2001 influenced by the Doli Incapax doctrine. This research uses a normative juridical method with a comparative approach to analyze the similarities and differences in both legal systems. The findings indicate that Indonesia emphasizes child rehabilitation through diversion mechanisms, whereas Malaysia adopts a more formal approach emphasizing court decisions. The study recommends policy improvements in both countries to enhance the protection of child offenders' rights.